(3fgGjI GdhUhd Edi Yde GdCUhds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3MSf Hf Ydj ThTJQjs)
(3ChdgG (B:s
(3GdMeO ddg GdebOS HhLhH hLhOg Yf GdCTHGg hGdfXGFQ(B...(3CeG HYO aEf Gddg TQa fhY GdEfSGf Ydi ZjQg ef GdeNdhbGJ(B...s
(3BNQgG (B:s
...(3hbO jMUd aj HGH GdJUOjbGJ hGdJUhQGJ JQLjMGJ cKjQI hjJQcH ef GdCfhGY JQLjMGJ CNQ hdG jNai JMUjd Pdc def dg COfi aWGfI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B227s
(3GdPQjYI(B:(3L(B24(3,U(B248(3,Qbe(B2160s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs